2022
DOI: 10.7759/cureus.30739
|View full text |Cite
|
Sign up to set email alerts
|

Management of Foreign Bodies in the Ear, Nose and Throat in Pediatric Patients: Real-Life Experience in a Large Tertiary Hospital

Abstract: Background: Foreign body (FB) injuries occur frequently in children. The aim of this paper is to provide an update on the experience of the Department of Otolaryngology, San Camillo Forlanini Hospital in Rome concerning the management of FB injuries in children.Methodology: This study was carried out by collecting data from the medical reports of our Pediatric Emergency Room stored between 2007 and 2021. Inclusion criteria were diagnosis of FB in pediatric patients based on the ENT evaluation. Pediatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
2
2
0
4
Order By: Relevance
“…Similar to another's studies [10,12], the ear FB was the most found in our study and include, seeds, grains, dolls eyes, erases, parts of plastic toys, cotton swabs, pebbles, sponges, beads typically African hairstyles and animated FB such as insects, cockroaches, larvae, etc. Occasionally it may be asymptomatic and found incidentally during routine ear examination or may have otalgia, pruritus, otorrhea, otorrhagia, tinnitus and hypoacusis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to another's studies [10,12], the ear FB was the most found in our study and include, seeds, grains, dolls eyes, erases, parts of plastic toys, cotton swabs, pebbles, sponges, beads typically African hairstyles and animated FB such as insects, cockroaches, larvae, etc. Occasionally it may be asymptomatic and found incidentally during routine ear examination or may have otalgia, pruritus, otorrhea, otorrhagia, tinnitus and hypoacusis.…”
Section: Discussionsupporting
confidence: 89%
“…Like other studies [11,12], males were the most affected, probably due to the more adventurous and curious spirit of this gender.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Önemli mortalite ve morbidite nedeni olabilen YC aspirasyonları bir yaşın altındaki çocuklarda üçüncü, üç yaşın altındaki çocuklarda ise dördüncü ölüm nedeni olarak bildirilmiştir. [4] Kulak burun boğaz YC olgularının en sık üç yaşta olmak üzere özellikle beş yaşın altındaki çocuklarda görüldüğü bildirilmiştir, bunun nedeni ise erken çocukluk döneminde çocukların çevrelerinde buldukları nesneleri keşfetme amacıyla kulak, burun ve boğazlarına yerleştirme eğiliminde olmaları ve yürümeyi öğrendikten sonra YC'ye ulaşmalarının daha kolay olmasıdır. Yaş ortalaması birçok çalışmada kulakta YC olanlarda burun ve boğazda YC olanlara kıyasla daha yüksek bulunmuş ayrıca YC olgularının erkek cinsiyette görülme sıklığının daha çok olduğu rapor edilmiştir.…”
Section: Discussionunclassified
“…As a matter of fact, foreign body ingestion and aspiration cause a considerable amount of morbidity and mortality because of choking; it is the fourth most common cause of unintentional death in children under three and the third youngest among those under one year old [ 15 ].…”
Section: Introductionmentioning
confidence: 99%